Migration of exsolved CO2 following depressurization of saturated brines. Issue 6 (16th October 2013) - Falta, Ronald W.; Zuo, Lin; Benson, Sally M.
Abstract Geologic disposal of supercritical CO2 in saline aquifers and depleted oil and gas fields will cause large volumes of brine to become saturated with dissolved CO2 at concentrations of 40 g/l or more. As CO2 dissolves in brine, the brine density increases slightly. This property favors the long‐term storage security of the CO2 because the denser brine is less likely to move upwards toward shallower depths. However, there are plausible mechanisms by which the CO2‐laden brine could be transported to a shallower depth, where the CO2 would come out of solution (exsolve), forming a mobile CO2 gas phase. Recent laboratory experiments of the exsolution process show that the CO2 phase relative permeability measured during exsolution is on the order of 1000 times lower than the relative permeability measured during a conventional CO2 core flood. Numerical simulations of upward brine migration through an open fault were performed using TOUGH2‐ECO2N with the two types of relative permeability functions. When traditional core flood relative permeabilities are used, upward flow of a CO2 saturated brine leads to exsolution and the development of a highly mobile CO2 gas phase. When relative permeabilities measured during exsolution are used, the tendency for the exsolved CO2 to migrate as a separate phase is greatly reduced, and the exsolved CO2 can partially block brine flow through the open fault. For the conditions considered, use of the exsolution relative permeability functions reduced the upward CO2 flux by about a factor of four compared to the case with core flood relative permeability functions. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd